Age nine is possible: Improving age 9 HPV initiation through a national quality improvement initiative during the COVID-19 pandemic - Jennifer Isher-Witt; Shaylen Foley; Anna Hassan; Amelia Sloan; Jennifer Nkonga; Marcie Fisher-Borne (Taylor & Francis Group, 2023)
ABSTRACTThe American Cancer Society collaborated with a range of healthcare partners in 2020-2022 to implement quality improvement clinical interventions with the goal of improving HPV vaccination rates among adolescents' ages 9-13. 2020 was the first cohort for which partners had been asked to submit HPV rate data for patients' ages 9-12. At least 80% of the partners across all reported project years were able and willing to report HPV rates for these ages. Partners submitted HPV initiation rates at the beginning and end of the 12-month project year along with project activities, including evidence-based interventions (EBIs) implemented. Mean initiation rates for ages 9-10 significantly increased 4.1% during 2020 compared to non-significant rate increases of 2.6% and 2.0% for ages 11-12 and age 13, respectively. In 2021, ages 9-10 initiation saw a non-significant increase of 2.2%, whereas ages 11-12 and age 13 decreased non-significantly by 0.3% and 0.1%, respectively. The 2022 cohort saw significant initiation rate increases of at least 4% across all ages, potentially a promising result of the myriad back on track HPV vaccination campaigns designed to reverse the damage of the COVID-19 pandemic on adolescent immunizations. These findings demonstrate an effective adaptation of quality improvement in increasing HPV vaccination coverage among younger ages even during a national pandemic.